กรณีศึกษาการหาจุดคุ้มทุนเพื่อออกแบบโรงไฟฟ้าแก๊สชีวภาพจากมูลโคนม - ต้นโพธิ์, สุทธินันท์; สุทธิสุวรรณ์, อรรถพร; โทนสูงเนิน, พิพัฒน์พงศ์; วงค์หาญ, วรวรรณ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2014)
บทคัดย่อ งานวิจัยฉบับนี้เป็นการศึกษาจุดคุ้มทุนเพื่อออกแบบโรงไฟฟ้าแก๊สชีวภาพจากมูลโคนม ที่ฟาร์มโคนม ขนาด 100 ตัว ในพื้นที่ 2 ไร่ จ.นครราชสีมา (พื้นที่สมมติ) โดยใช้บ่อหมักแก๊สขนาด 100 ลูกบาศก์เมตร เครื่องกำเนิดไฟฟ้าแก๊สชีวภาพขนาด 22 กิโลวัตต์ ในการผลิตไฟฟ้าเพื่อขายให้กับการไฟฟ้าส่วนภูมิภาค จำนวน 5 ชม./วัน โดยการอุดหนุนรับซื้อไฟฟ้ารัฐบาลเป็นรูปแบบของ Adder ราคารับซื้อไฟฟ้า 3.128 บาท/กิโลวัตต์ วิเคราะห์รายได้ทั้งหมด 223,224.- บาท ระยะเวลาการคืนทุน 3.2 ปี คำสำคัญ : การศึกษาจุดคุ้มทุนเพื่อออกแบบโรงไฟฟ้าแก๊สชีวภาพจากมูลโคนม Abstract This Research presents the breakeven point for the design of the biogas power plant from dairy manure. The dairy farm of 100 in the typical area of 2 rai at Nakonrachasima province, Digester using 100 tons of fuel for generators, biogas blue size 22 kW To produce electricity for sale to the Provincial Electricity Authority. for 5 hr / day. By the subsidies been power purchase government is a form of Adder. Electricity price selling at 3.128 Baht/kWh Investment cost for Biogas power plant size of 22 kW is 223,224 Baht. Payback period is 3.2 years. Keywords : The breakeven point for the design of the biogas power plant from dairy manure.